Deep Structures of Religious Moderation in Higher Education: An Analysis Through the Perspectives of Iceberg Theory and Theory U - Yuberti, Yuberti; Jamaluddin, Wan; Irfani, Bambang; Susilowati, Nur Endah; Anugrah, Adyt (Universitas Islam Negeri Ar-Raniry, 2026)
This study investigates the implementation of religious moderation policies across three state religious higher education institutions in Indonesia through the conceptual lenses of the Iceberg Model and Theory U. It aims to explore the visible practices and underlying institutional structures, behavioral patterns, and mental models that shape the implementation of religious moderation. A qualitative multiple-case study design was employed between July and September 2024. The study involved 200 purposively selected participants, comprising students, lecturers, and administrative staff from three participating institutions. Data were collected through semi-structured interviews, non-participant observations, document analysis, and a descriptive questionnaire used to support data triangulation. Qualitative data were analyzed inductively using thematic analysis and subsequently interpreted through the Iceberg Model and Theory U. The findings indicate that the participating institutions adopted different approaches to implementing religious moderation. One institution demonstrated stronger formal institutional support through documented policies, dedicated organizational structures, and structured training programs, whereas the other institutions relied more on community engagement and everyday interactions within religiously diverse environments. Despite these differences, all institutions faced structural challenges, including limited inclusive facilities and insufficient institutional mechanisms to sustain interfaith engagement. The study concludes that effective implementation of religious moderation requires the integration of formal institutional governance with community-based learning and continuous organizational reflection. These findings contribute to a deeper understanding of religious moderation as an institutional process and provide practical insights for strengthening governance and inclusive campus culture in religious higher education.